2020
DOI: 10.1111/jsr.13076
|View full text |Cite
|
Sign up to set email alerts
|

Temporal associations between morningness/eveningness, problematic social media use, psychological distress and daytime sleepiness: Mediated roles of sleep quality and insomnia among young adults

Abstract: The extant literature has suggested relationships between an individual's chronotype (in relation to morningness/eveningness) and several outcomes, including addictive disorders, psychological distress and daytime sleepiness. Moreover, sleep quality has been proposed to be a mediator in the aforementioned relationships. Consequently, the aim of the present study was to investigate the complex relationship between morningness/eveningness, problematic social media use, psychological distress and daytime sleepine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 46 publications
3
17
1
Order By: Relevance
“…Furthermore, in the FMS patients with greater sleep disorders, the FMS disease severity and pain scores were determined to be higher. Interestingly, contrary to previous studies, this study did not find a significant relationship between sleep disorders and social media addiction [34][35][36]. This may be because previous studies included people who did not have FMS or any disease and found that excessive social media use causes sleep disturbance.…”
Section: Discussioncontrasting
confidence: 98%
“…Furthermore, in the FMS patients with greater sleep disorders, the FMS disease severity and pain scores were determined to be higher. Interestingly, contrary to previous studies, this study did not find a significant relationship between sleep disorders and social media addiction [34][35][36]. This may be because previous studies included people who did not have FMS or any disease and found that excessive social media use causes sleep disturbance.…”
Section: Discussioncontrasting
confidence: 98%
“…90,91 In addition, smoking dependence causes physiological craving for nicotine, subsequently waking the individual, disturbing the sleeping pattern, and leading to insomnia. 92 95 Also, Internet addiction mediated the link between SM use and depression and anxiety. 96 Having said that, no past study has examined the possible mediation of stress between PSMU and depression, anxiety, and insomnia.…”
Section: Insomnia and Psmumentioning
confidence: 98%
“…These very popular and attractive sites are designed to keep users engaged and for many individuals their use can be habitual and/or excessive taking time away from activities that may be more important such as educational and/or occupational duties. Consequently, excessive social media use, like other types of excessive use such as excessive internet or smartphone use, may cause a variety of health problems, including sleep problems, musculoskeletal discomfort, mood issues and impaired daily functions, as well as addiction‐like consequences in a small minority of individuals 27‐36 …”
Section: Introductionmentioning
confidence: 99%